Study on Pore and Fissure Structure Characteristics of Deep Soft Coal Rock - Minbo Zhang; Zhen Zhang; Dangyu Zhang; Delong Zou; Jinlei Du; Zichao Wang; Chunxin Li (Geofluids)
The microscopic pore and fissure structure is the key factor affecting the exploitation, storage, and migration of coalbed methane and coal spontaneous combustion tendency. For further research of the microstructure of deep soft coal rock, such as pores and fissures, the coal samples from the Yangdong mining area were qualitatively and quantitatively analyzed in terms of morphological characteristics, pore shape, pore specific surface area, pore volume, and pore diameter by a scanning electron microscope (SEM) and a low-temperature liquid nitrogen adsorption experiment. The results show that there are three major categories and five minor categories of pores with different genetic types, including metamorphic pore, exogenous pore, and mineral pore, and there are endogenous fissures, exogenous tensile fissures, and exogenous shear fissures developed in the coal body. According to the results of the low-temperature liquid nitrogen adsorption experiment, the hysteresis curves of coal samples can be divided into two types. The I type curve produces a loop. There is a “hysteresis loop” which is obvious, and there is an inflection point that is not obvious. The pore system is mainly composed of open pores. The II type curve has no adsorption back line and no obvious inflection point. The pore structure is mainly composed of an impermeable hole closed at one end. The BET specific surface area of coal samples ranges from 0.2810 to 4.7569 m2/g, with an average of 1.27984 m2/g. The BJH pore volume ranges from 0.002864 to 0.007377 cm3/g, with an average of 0.0041246 cm3/g. The average BJH pore diameter of coal samples ranges from 4.3935 to 20.1501 nm, with an average of 16.0313 nm. The pore specific surface area of coal is mainly contributed by micropores, and the transition pores contribute the most to pore volume. The distribution of pore volume in each pore section of a coal sample has the rule that the transition pore is larger than the micropore, and the micropore is larger than the mesopore, and the maximum ratio is 66.2%. The distribution of pore specific surface area has the rule that the micropore is larger than the transition pore, and the transition pore is larger than the mesopore. The maximum ratio is 91.2%.